Strategic response for ease of doing business using case-based reasoning. (30th December 2022) - Wang, Yameng; Wang, Xiaolei; Feng, Yuqiang; Liu, Luning
Abstract: Sound ease of doing business is essential for building a modernized economy and fostering high-quality growth. Research on the ease of doing business should not only focus on the impact and evaluation system, but also have guiding significance for decision-making related to the ease of doing business, but there are still relatively few studies in this area. Due to the complexity of ease of doing business, to save energy and make the most of the experience knowledge of decision-makers, we have introduced case-based reasoning (CBR) into strategy response, as a possible application of the analysis of case histories. The purpose of this paper is to propose a CBR strategy response method for ease of doing business, which can be used to formulate more intelligent and efficient ease of doing business strategy. The innovation of this research focuses on three key parts. Firstly, a CBR strategy response method for ease of doing business is innovatively developed. Secondly, the ontology method is used to build ease of doing business domain model, including city features, ease of doing business indicators, and response strategy. Thirdly, Missing values are also included in the calculation process. During the calculation process, missing values are also processed, and inappropriate response strategies in similar case sets are adjusted in response to differences between scenarios to generate feasible strategies. Finally, a case study of a city shows that this method can extend the CBR approach to ease of doing business strategy response. Highlights: A CBR-based doing business strategy response method is innovatively developed. Using ontology approach to build an easy of doing business domain model. A two-step case retrieval method is proposed and missing values are dealt with. A scenario-based case reuse method is proposed and used.